P126 The prevalence of self reported respiratory symptoms and diagnoses amongst patients attending a drug dependance clinic. (14th November 2013) - Tridimas, A; Archer, T; Rehman, Z; Oelbaum, S; Burhan, H
Abstract : Introduction: In England it is estimated that between the ages of 15–64, 2.2% use cocaine, 6.8% use cannabis and 0.8% use opiates on a regular basis 1 . Illicit drug use such as crack cocaine smoking, heroin smoking and intravenous heroin also contribute to a range of respiratory conditions. A significant proportion of drug users also smoke tobacco. For a wide range of social, psychological and economic reasons, respiratory conditions within this population may often go undiagnosed for many years. Often their disease can progress to become severe before any medical input is sought. Aim: To ascertain a detailed tobacco and non-tobacco smoking history and the prevalence of respiratory symptoms, prior diagnostic investigations and diagnoses amongst clients in the criminal justice system attending an inner city drug treatment clinic run by Addaction. Methods: Questionnaires were administered by Addaction staff and junior doctors from the respiratory department as part of a service evaluation. In order to ascertain whether their symptoms were likely to represent underlying COPD, a validated questionnaire was used 5 . The definitive diagnostic test for COPD is spirometryhowever in this particular group of people this is difficult to obtain due to frequently chaotic lifestyles. Results: A total of 62 clients completed questionnaires. 44 (71%) smoked cigarettes, 39 (63%) tobacco (mean pack years (SD) combined cigarettes/tobacco 23.5 (25)), 40 (65%) marijuana, 54 (87%) crack and 57 (92%) heroin. 26 clients (42%) injected heroin. Only 17 (24%) reported having had spirometry. Clients were divided into tertiles ('heavy', 'moderate' and 'mild' exposure to smoked tobacco and drugs) according to total smoking history (combined pack years, joints/day years, rocks/day years and bags/day years respectively for tobacco, marijuana, crack and heroin). There were no statistically significant differences between groups - See Table 1 . Conclusions: The majority of the clients reported at least one symptom suggestive of airways disease. A larger study incorporating spirometry based at drug clinics may haelp to diagnose, and thereby facilitate effective treatment, of underlying COPD in this population. Early diagnosis and treatment could reduce illness within this population, prevent admissions and lead to significant savings in NHS spending. References: United Nations Office on Drugs and Crime, World Drugs report 2012 Pulmonary effects of illicit drug use, Clin Chest Med . 2004 Mar;25(1):203–16, Wolff AJ et al . 5. Scoring System and Clinical Application of COPD Diagnostic Questionnaires, CHEST . June 2006;129(6):1531–1539. doi:10.1378/chest.129.6.1531, Price DB et al .